PENGEMBANGAN KOMIK BERBASIS PENDIDIKAN LINGKUNGAN HIDUP UNTUK MENINGKATKAN KEMAMPUAN LITERASI PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS III SDN 24 RABANGODU UTARA KOTA BIMA - Aulia Imaniar; Muh.Rijalul Akbar; Rakhmatul Ummah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to develop environmental education-based comic media as an alternative to learning Indonesian for grade III students of SDN 24 Rabangodu Utara, Bima City. The background of this study is based on the low literacy skills of students and the minimal use of interesting and contextual learning media. Comics were chosen because they are able to present material visually and narratively, so that they can increase students' interest in reading, understanding of texts, and environmental awareness. Through the development of this media, it is hoped that the learning process will be more enjoyable, effective, and support the improvement of literacy and environmental care characters from an early age. The methodology used is research and development (Research and Development) by adopting the ADDIE model as a framework. The subjects of this study were 16 grade III students of SDN 24 Rabangodu Utara, Bima City, with variables of environmental education-based comic media and literacy skills and research instruments used in the form of questionnaires, interviews, documentation, and pretest posttest tests. The results of the media feasibility test showed a very feasible percentage (85%), while the practicality test from teachers and students was very good (90% and 92%). The effectiveness analysis showed N-Gain .83 (quite effective category). It was concluded that the environmental education-based comic media that was developed was quite effective in increasing the literacy skills of class III students at SDN 24 Rabangodu Utara, Bima City.